The effect of ground motion characteristics on the fragility analysis of reinforced concrete frame buildings in Australia. (December 2021) - Alothman, Aya; Mangalathu, Sujith; Hashemi, Javad; Al-Mosawe, Alaa; Alam, M.D. Morshed; Allawi, Abbas
Highlights: Fragility analysis of buildings under near-fault, short and long-duration earthquakes. Exploring vulnerable low to mid-rise RC building types in Australia. Using OpenSees for the seismic performance assessment of a multi-story RC building. Calibrating experimental results to the IMK model to capture the hysteretic response. Recommending ground motion characteristics for seismic performance assessment. Abstract: The seismic performance of buildings can be assessed through fragility analysis as it yields the probability of the demand exceeding the capacity at a specified level of intensity. Although it's well-identified that earthquake uncertainties dominate the fragility characteristics, the influence of the characteristics of the earthquake on the fragility analysis is not well investigated. This study aims to compare the effect of earthquake characteristics on the fragility values of typical buildings in Australia. To achieve this, a typical reinforced concrete building is selected and modeled using a finite element approach. Various ground motion suites, such as near-fault, far-fault, and long-duration are selected, and the fragility analysis has been carried out for each ground motion suite. It is observed that the variation in the median values of the collapse fragilities can be as high as 48% between short-duration and long-duration ground motions, and about 40% between long-duration and pulse-like ground motions.